Research on public network and private network diversion scheme for 4G/5G users - MA Hongyuan; FENG Zheng; ZHOU Wei; SONG Xuguang; YANG Xiaole (Dianxin kexue)
Facing the demand of 4G/5G users accessing public network services and private network services simultaneously, the limitations of the existing technical schemes in the industry were reviewed, and a network-side non-inductive diversion scheme was proposed. It only needed to establish a public network IP service channel by the UE. When the network detected that users used private network services, a private network IP service channel for users on the network side was established by SMF/PGW-C to divert the private network services of users. There was only one IP channel in the mobile phone terminal to transmit public network services and private network services, corresponding to one public network IP channel and one private network IP channel on the network side, and SMF/PGW-C completed the mapping and splicing of the user-side IP channel and the corresponding network-side public network IP channel and private network IP channel, as well as the replacement of the user’s IP address, thus realizing the diversion of the user’s public network services and private network services. This scheme not only meets the demand of dual-domain private network services, but also allows for the separate management and charging of users’public network service IP channels and private network service IP channels by the network side, and has no additional requirements for terminals.